2018
DOI: 10.5194/acp-18-13773-2018
|View full text |Cite
|
Sign up to set email alerts
|

Observing local CO<sub>2</sub> sources using low-cost, near-surface urban monitors

Abstract: Abstract. Urban carbon dioxide comprises the largest fraction of anthropogenic greenhouse gas emissions, but quantifying urban emissions at subnational scales is highly challenging, as numerous emission sources reside in close proximity within each topographically intricate urban dome. In attempting to better understand each individual source's contribution to the overall emission budget, there exists a large gap between activity-based emission inventories and observational constraints on integrated, regional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
2
31
1
Order By: Relevance
“…More recent studies have collected data to complement existing monitoring efforts (i.e., or have been operating as a sub network within a larger national network). These were in many cases associated with human health (Rogulski, 2018) or climate impacts (Shusterman et al, 2018;Šećerov et al, 2019) or had direct economic implications, for example through flooding (Horita et al, 2015) or fishing livelihoods (Wada et al, 2007). It should be noted that very few studies embraced the principles of open science and open data more generally (however see Rettig et al, 2014;Jones et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have collected data to complement existing monitoring efforts (i.e., or have been operating as a sub network within a larger national network). These were in many cases associated with human health (Rogulski, 2018) or climate impacts (Shusterman et al, 2018;Šećerov et al, 2019) or had direct economic implications, for example through flooding (Horita et al, 2015) or fishing livelihoods (Wada et al, 2007). It should be noted that very few studies embraced the principles of open science and open data more generally (however see Rettig et al, 2014;Jones et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Low-cost technology has also been adopted in GHG research. Studies have utilized low-cost sensors to monitor atmospheric concentrations of CO2 (Shusterman et al, 2018) and CH4 (Riddick et al, 2020;Collier-Oxandale et al, 2018;Eugster et al, 2012) and to measure CO2 fluxes with chambers (Bastviken et al, 2020 and2015;Brändle and Kunert, 2019;Martinsen et al, 2018). Some studies have also demonstrated how to build low-cost gas sampling and analysis instruments (Carbone et al, 2019;Martinsen et al, 2018;Bastviken et al, 2015).…”
Section: Greenhouse Gas Fluxmentioning
confidence: 99%
“…The feasibility of deploying dense monitoring networks has increased with the availability of inexpensive sensors, although questions about sensor accuracy continue to be studied (e.g., Borrego et al, 2016;Castell et al, 2017;Li and Biswas, 2017;Schneider et al, 2017;Lim et al, 2019). Approaches that combine mobile monitoring with measurements made at stationary monitoring locations (Adams et al, 2012;Simon et al, 2018) or with modeling (Messier et al, 2018) are being actively researched.…”
Section: Introductionmentioning
confidence: 99%